2011
DOI: 10.4137/cmo.s5072
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Management of Relapsed Small-Cell Lung Cancer with Amrubicin Hydrochloride

Abstract: Lung cancer is the leading cause of cancer death, and approximately 15% of all lung cancer patients have small-cell lung cancer (SCLC). Although second-line chemotherapy can produce tumor regression, the prognosis is poor. Amrubicin hydrochloride (AMR) is a synthetic anthracycline anticancer agent and a potent topoisomerase II inhibitor. Here, we discuss the features of SCLC, the chemistry, pharmacokinetics, and pharmacodynamics of AMR, the results of in vitro and in vivo studies, and the efficacy and safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…These observations suggest that the induction pathway of topoisomerase II is more sensitive to indisulam than the regulation pathway of steady-state topoisomerase II . Similarly, synergism has been reported with combinations of topoisomerase I inhibitors and topoisomerase II inhibitors [26]. Mammalian DNA topoisomerase II is the primary target of a number of antitumor agents, such as doxorubicin, daunorubicin, VP-16, and amsacrine [27].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that the induction pathway of topoisomerase II is more sensitive to indisulam than the regulation pathway of steady-state topoisomerase II . Similarly, synergism has been reported with combinations of topoisomerase I inhibitors and topoisomerase II inhibitors [26]. Mammalian DNA topoisomerase II is the primary target of a number of antitumor agents, such as doxorubicin, daunorubicin, VP-16, and amsacrine [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a randomised phase III trial, topotecan demonstrated a survival advantage against best supportive care [31]; and in a randomised trial against CAV, topotecan was at least equally effective [52]. Other substances which have demonstrated at least some efficacy in trials are listed in table 7, and include paclitaxel, gemcitabine and pemetrexed [17,35,37,38,43,54].…”
Section: Relapse and Further-line Therapymentioning
confidence: 99%
“…Amrubicin acts by inhibiting topoisomerase II, and is often compared with the topoisomerase I inhibitor topotecan in clinical trials [54]. The efficacy of amrubicin in Caucasian patients remains unclear, a difference which may be due to ethnic variations in enzymatic metabolism [73].…”
Section: Newer Chemotherapeutic Agentsmentioning
confidence: 99%
“…4 Despite the good response of first line chemotherapy in SCLC, patients generally relapse early and therapeutic options in second line treatment are limited. In sensitive disease, topotecan, which is the current standard second line treatment in Europe, irinotecan and amrubicin have shown modest activity as monotherapy, [5][6][7] while doxorubicin and ifosfamide were revealed not to be effective in refractory relapse. 8,9 Given the disappointing results in second line therapy, new therapeutic approaches are desperately needed in the field of SCLC.…”
Section: Introductionmentioning
confidence: 99%